U-SMILE: a brief version of the Short Multidimensional Inventory on Lifestyle Evaluation - Raquel B. De Boni; Jurema C. Mota; Felipe Barreto Schuch; Daniel Alvarez Pires; Thiago Sousa Matias; Renato Sobral Monteiro-Junior; Andrea C. Deslandes; Danilo R. Silva; Helena Ferreira Moura; Nicole Galvão-Coelho; Fabianna Resende de Jesus-Moraleida; Flavio Kapciznki; et al. (Trends in Psychiatry and Psychotherapy)
Abstract Objective Lifestyle Medicine comprises six domains: diet, substance use, physical activity, stress management, social connection, and sleep. The comprehensive assessment of lifestyle is challenging, but the Short Multidimensional Inventory on Lifestyle Evaluation (SMILE) was developed to fill out this gap. In this paper, we describe the development and the psychometric properties (internal consistency, concurrent and convergent validity) of a shorter version of the SMILE among university students. Methods Data from a cross-sectional study including 369 students from 10 Brazilian universities were used. Considering a theoretical nomological net, we performed exploratory factor analysis (EFA) to obtain the most parsimonious, interpretable, and good-fitting model. Results The final model was called U-SMILE, comprised 24 items, and presented acceptable internal consistency (Cronbach's α = 0.73, McDonald's ω = 0.79). To evaluate the concurrent validity of the U-SMILE, we compared it to the original SMILE and found a high correlation between the instruments (Spearman's r = 0.94). Furthermore, we evaluated convergent validity by examining the U-SMILE correlation with the Patient Health Questionnaire (PHQ-9) (Spearman's r = −0.517), and Generalized Anxiety Disorder Questionnaire (GAD-7) (Spearman's r = −0.356), two validated instruments to screen for depression and anxiety, respectively. Conclusion Our findings suggest that the U-SMILE is a valid instrument for assessing lifestyle among university students. We recommend that the use of U-SMILE to evaluate overall lifestyle scores rather than individual domain scores. Finally, we discuss the importance of clarifying the definitions of lifestyle and related constructs in future research.